Diabetes in pregnancy masterclass 'Navigating the Bumps' - Mohamed Shah, Fatimah Zaherah; Awang, Mohd Hazriq; Eddy Warman, Nur Aini; Fadilah, Aimi; Abdul Ghani, Rohana (Faculty of Medicine, 2024)
The incidence of diabetes mellitus (DM) in Malaysia continues to increase at an exponential rate, with significant rises in the younger, childbearing population. This was illustrated clearly in the latest Malaysian National Health and Morbidity Survey on Maternal and Child Health 2022, which highlighted that the incidence of diabetes in pregnancy was 27.1%, constituting an almost 15% increase in the incidence within a 5-year period.